USING GCMS TO FIND OUT THE VOLATILE COMPONENTS IN THE AROMA OF THREE DIFFERENT COMMERCIAL FRUITS IN CHINA - W. Jaleel; 4; Q. Li; Q. Shi; G. Qi; M. Latif; S. Ali; N. A. Yasin; L. Lyu; Y. He (Journal of Animal and Plant Sciences, 2020)
The agricultural sector is an essential source of income and food for humans. Fruits are important sources of nutrients, vitamins, essential elements, and as well as the source of income for humans. Volatile components make the aroma of fruit and fruit species and cultivars. However, the knowledge and information about volatile components or volatile profiles are essential, because these aroma components make fruit delicious to humans and as well as attract or repel insect pests. And the identification of volatile components from fruits is very important to a better understanding of the impact of climatic conditions. To the best authors knowledge, in this study, we reported the first time volatile profile of unidentified cultivar of mango (Mangifera indica L. Hanana Datai Nong Mang), guava (Psidium guajava Linn. China Pear), and banana (Musa acuminata L. Dwarf banana or Fen Jiao) fruits and these fruits are commercially selling and growing in China. The Headspace Solid-phase Microextraction (HS-SPME) and porapak Q coupled with gas chromatography-mass spectrometry analysis (GC-MS) were used to identify the volatile profiles of each fruit cultivar. A total of 10, 15, and 23 volatile components/compounds were identified from mango, guava, and banana fruits, respectively. The major constitution of volatile components obtained from mango, guava, and banana was 3-carene, caryophyllene, and cycloheptasiloxane, tetradecamethyl-.
Keywords: Banana; 3-carene; caryophyllene; cycloheptasiloxane; components; tetradecamethyl-; GC-MS; guava; mango; volatile components.